The Effect of Nicotinamide on Gene Expression in a Traumatic Brain Injury Model - Anderson, Gail D.; Peterson, Todd C.; Farin, Fred M.; Bammler, Theo K.; Beyer, Richard P.; Kantor, Eric D.; Hoane, Michael (Frontiers in Neuroscience, 2013)
Microarray-based transcriptional profiling was used to determine the effect of nicotinamide on gene expression in an experimental traumatic brain injury (TBI) model. Ingenuity Pathway Analysis (IPA) was used to evaluate the effect on relevant functional categories and canonical pathways. At 24 h, 72 h and 7 days, respectively, 70%, 58% and 76%, of the differentially expressed genes were up-regulated in the vehicle treated compared to the sham animals. At 24 h post-TBI, there were 150 differentially expressed genes in the nicotinamide treated animals compared to vehicle; the majority (82%) down-regulated. IPA analysis identified a significant effect of nicotinamide on the functional categories of cellular movement, cell-to-cell-signaling, antigen presentation and cellular compromise, function and maintenance and cell death. The canonical pathways identified were signaling pathways primarily involved with the inflammatory process. At 72 h post-CCI, there were 119 differentially expressed genes in the nicotinamide treated animals compared to vehicle; the majority (90%) was up-regulated. IPA analysis identified a significant effect of nicotinamide on cell signaling pathways involving neurotransmitters, neuropeptides, growth factors and ion channels with little to no effect on inflammatory pathways. At 7 days post-TBI, there were only 5 differentially expressed genes with nicotinamide treatment compared to vehicle. Overall, the effect of nicotinamide on counteracting the effect of TBI resulted in significantly decreased number of genes differentially expressed by TBI. In conclusion, the mechanism of the effect of nicotinamide on secondary injury pathways involves effects on inflammatory response, signaling pathways and cell death.